Quality of social and emotional wellbeing services for families of young Indigenous children attending primary care centers; a cross sectional analysis - Karen M. Edmond; Kimberley McAuley; Daniel McAullay; Veronica Matthews; Natalie Strobel; Rhonda Marriott; Ross Bailie (BMC, 2018)
Abstract Background The quality of social and emotional wellbeing services for Indigenous families of young children is not known, in many settings especially services provided by primary care centers. Methods Our primary objective was to assess delivery of social and emotional wellbeing services to the families of young (3-11 months) and older (12-59 months) Indigenous children attending primary care centers. Our secondary objective was to assess if delivery differed by geographic location. Two thousand four hundred sixty-six client files from 109 primary care centers across Australia from 2012 to 2014 were analysed using logistic regression and generalised estimating equations. Results The proportion of families receiving social and emotional wellbeing services ranged from 10.6% (102) (food security) to 74.7% (1216) (assessment of parent child interaction). Seventy one percent (71%, 126) of families received follow up care. Families of children aged 3-11 months (39.5%, 225) were more likely to receive social and emotional wellbeing services (advice about domestic environment, social support, housing condition, child stimulation) than families of children aged 12-59 months (30.0%, 487) (adjusted odds ratio [aOR] 1.68 95% CI 1.33 to 2.13). Remote area families (32.6%, 622) received similar services to rural (29.4%, 68) and urban families (44.0%, 22) (aOR 0.64 95% CI 0.29, 1.44). Conclusions The families of young Indigenous children appear to receive priority for social and emotional wellbeing care in Australian primary care centers, however many Indigenous families are not receiving services. Improvement in resourcing and support of social and emotional wellbeing services in primary care centers is needed.